TECHNOLOGIES FOR DEVELOPING DIGITAL COMPETENCE OF STUDENTS IN TEACHING ENGLISH - Dadaxonova Mohlaroy (Web of Journals Publishing, 2024)
This article explores the transformative role of language learning apps in contemporary education, emphasizing their influence on digital competence and language proficiency. Examining popular apps like Duolingo, Babbel, and Rosetta Stone, the article delves into their gamified approaches, adaptive learning algorithms, and anytime, anywhere accessibility. It discusses how these apps motivate active engagement, provide personalized learning experiences, and cater to diverse learning styles. Furthermore, the article highlights the flexibility, convenience, and differentiated instruction facilitated by language learning apps, ultimately positioning them as powerful tools in cultivating confident and effective communicators in the globalized 21st-century landscape.
Keywords: Language Learning Apps, Duolingo, Babbel, Rosetta Stone, Digital Competence, Language Proficiency, Gamification, Adaptive Learning, Personalized Learning, Anytime Anywhere Accessibility, Differentiated Instruction, Modern Education, Global Communication.